Antibodies to rabbit progesterone receptor: crossreaction with human receptor. - Logeat, F (1981)
Progesterone receptor from rabbit uterine cytosol was purified to a specific activity of approximately 2 nmol of bound hormone per mg of protein. A goat was immunized with this preparation and, after two injections of 0.7-0.8 nmol, yielded antireceptor antibodies. The antiserum reacted with both cytosolic and nuclear rabbit progesterone receptor and also with progesterone receptor from other rabbit tissues (vagina and pituitary). A crossreaction was observed with progesterone receptors from other mammalian, especially human, tissues (cytosolic receptor from rat and guinea pig uterus, cytosolic receptor from human breast cancer, and nuclear receptor from human endometrium). On the contrary, there was no interaction with a nonmammalian receptor (chicken oviduct progesterone receptor). The antibodies did not crossreact with other rabbit steroid receptors (uterine estradiol receptor and liver glucocorticoid receptor) or with nonreceptor progesterone-binding proteins (transcortin from plasma and uteroglobin from uterine fluid).